Rationale of Evaluation of Potency in Medicolegal Cases of Sexual Assault by Penile Color Doppler with Injection of Papaverine. - Shilpa Domkundwar1, Varsha V Jadhav2, Sonal Khandelwal3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Impotency in male is inability to develop or maintain a sufficient penile erection to conclude the act of intercourse to orgasm and ejaculation. The question of potency arises in many lawsuits in civil and criminal courts. In India, potency testing which includes penile color doppler with injection papaverine is done for all accused of sexual assault as a blanket rule. Penile color doppler with injection papaverine has its own limitations and side effects. Our study therefore aims to analyze and ascertain the justification of subjecting each accused of sexual assault to penile color doppler with injection papapverine.Aims and Objectives:1. To analyse whether evaluating potency in every medico legal case of sexual assault referred to our department using color doppler with injection papaverine is justified.2. To recommend changes based on our study.Method: This study is a retrospective analysis of data of 166 accused of sexual assault, between the period of May 2015-April 2018. Baseline ultrasound and penile color doppler assessment of erection following papaverine injection was done.Results: Procedure was performed on 166 accused of sexual assault, of whom the, 3 (1.80%) had arterial insufficiency. 6 (3.61%) accused on whom the procedure was performed developed priapism as complication. The rate of complications was found to be double than the positive result of the procedure.Conclusion: We conclude from our study that, due to limited role and complications of penile doppler and change in the definition of rape and laws related to it, overburdened health infrastructure of our country, every accused of sexual assault should not be subjected to penile color doppler study